Superconductivity and Cooper Pairs - Subedi, Mitramani Subedi (Himalayan Physics, 2017)
In this article, some crucial information is given in regard to superconductivity. The advancement in high temperature superconductivity is believed to solve the problem of energy crisis. So, intensive research in this part of physics is recommended. Actually, Cooper pairs of electrons are responsible for superconductivity. The Himalayan Physics Vol. 6 & 7, April 2017 (104-107)